Answer:
The answer is 144.
Step-by-step explanation:
Cause, 6 x 6 for the square is 36. For the triangle, 9 x 6 is 54, and 54 divided by 2 is 27. 27 x 4 is equal to 108. Now, we just add 108 and 36 to make 144.
Answer:
a) 3x⁴-4x³-8x²-35x-10
Step-by-step explanation:
3x2(x²-3x-1)+5x(x²-3x-1)+10(x²-3x-1)
3x⁴-9x³-3x²+5x³-15x²-5x+10x²-30x-10
3x⁴-9x³+5x³-3x²-15x²+10x²-5x-30x-10
3x⁴-4x³-8x²-35x-10
![\frac{4}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%7D%7B1%7D%20)
×
![\frac{2}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B3%7D%20)
=
![\frac{8}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B8%7D%7B3%7D%20)
You then divide the numerator(top) by the denominator(bottom)
![\frac{8}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B8%7D%7B3%7D%20)
=
![2 \frac{2}{3}](https://tex.z-dn.net/?f=2%20%5Cfrac%7B2%7D%7B3%7D%20)
Your answer is
Answer:
x= 4, -1
Step-by-step explanation:
-2x - 2 + x^2 + x + 180 - 2x - 2 = 180
add like terms and put in descending order
x^2 - 3x + 176 = 180
subtract 180 from both sides
x^2 - 3x - 4 = 0
factor out the equation
(x-4)(x+1)=0
solve for x
x-4=0 x+1=0
x=4 x=-1